Glacitectonic evidence of ice sheet interaction and retreat across the western part of Dogger Bank (North Sea) during the Last Glaciation. Issue 1 (February 2022) - Phillips, Emrys; Johnson, Kirstin; Ellen, Rachael; Plenderleith, Gayle; Dove, Dayton; Carter, Gareth; Dakin, Nicola; Cotterill, Carol
Abstract: High-resolution 2D seismic data from the western side of Dogger Bank (North Sea) has revealed that the glacigenic sediments of the Dogger Bank Formation record a complex history of sedimentation and penecontemporaneous, large-scale, ice-marginal to proglacial glacitectonism. The resulting complex assemblage of glacial landforms and sediments record the interplay between two separate ice masses revealing that Late Devensian ice sheet dynamics across Dogger Bank were far more complex than previously thought, involving the North Sea lobe of the British and Irish Ice Sheet, advancing from the west, interacting with the Dogger Bank lobe which expanded from the north. The active northward retreat of the Dogger Bank lobe resulted in the development of a complex assemblage of arcuate thrust-block moraines (≤ 15 km wide, > 30 km long) composed of highly folded and thrust sediments, separated by sedimentary basins and meltwater channels filled by outwash. The impact of the North Sea lobe was restricted to the western margin of Dogger Bank and led to deep-seated (100–150 m thick) glacitectonism in response to ice-push from the west. During the earlier expansion of the North Sea lobe, this thrust and fold complex initially occupied a frontal marginal position changing to a more lateral ice-marginal position as the ice sheet continued to expand to the south. The complex structural relationships between the two glacitectonic complexes indicates that these ice masses interacted along the western side of Dogger Bank, with the inundation of this area by ice probably occurring during the last glaciation when the ice sheets attained their maximum extents.